Etude Ethnobotanique Sur L’utilisation De Mentha Pulegium, Mentha Piperita Et Pelargonium Graveolens Au Nord Du Maroc (Taounate) Et Évaluation De Leur Pouvoir Antimicrobien - Chraibi, M.; Fikri-Benbrahim, K.; Amrani, M.; Farah, A.; Bari, A.; Ouaritini, Z. Benziane (European Scientific Journal, ESJ, 2018)
Traditional medicine has always occupied an important place in Moroccan traditions medication, Taounate region is concrete example. Thus, this survey aims to highlight the different uses of Mentha pulegium, Mentha piperita and Pelargonium graveolens in Taounate city during April month 2017, and to evaluate their antimicrobial potency against Staphylococcus epidermidis and Acinetobacter baumannii by microdilution method. A questionnaire was used with residents, herbalists and phytotherapists. The results showed that these three plants are used mainly for their therapeutic virtues; precisely against digestive disorders representing the most cited diseases for Mentha piperita (51%), respiratory diseases for Mentha pulegium (50%) and dermatological conditions for Pelargonium graveolens(44%). The majority of remedies are prepared by decoction (56%) from leaves (71%) and usually orally administered (68%) as herbal tea (58%). Cure rate is 41% with 53% health improvement. In addition, the essential oils of these studied plants exhibited strong inhibitory effect against all tested microorganisms with minimum inhibitory concentrations ranging from 0.01562% to 1% (v/v).